With or Without Him? Experimental Evidence on Gender-Sensitive Cash Grants and Trainings in Tunisia - Gazeaud, Jules; Khan, Nausheen; Mvukiyehe, Eric; Sterck, Olivier (World Bank, Washington, DC, 2022)
Is it possible to stimulate women’s employment by relaxing their financial and human capital constraints Does involving husbands help or hinder the effort Using an experiment in Tunisia, this paper shows that providing cash grants and financial training to women stimulates their income generating activities, but only when their partners are not involved. The program did not alter traditional gender roles. Instead, it encouraged employment of other household members and investments in small-scale agriculture and livestock farming — two activities traditionally undertaken by women at home. The impacts on household living standards are overwhelmingly positive, and suggest that the program is highly cost-effective.